The effects of xylitol chewing gum on oral environment among malaysian infantry personnel involved in military operation - Ramli, Hafsah Othman (2012)
Oral health is an important aspect of combat readiness in the armed forces. However, certain conditions during military operation can hinder oral hygiene practice and expose military personnel to oral health problem. Many studies have consistently showed positive potential of xylitol chewing gums as a preventive strategy in maintaining oral health. OBJECTIVE: To study the effects of xylitol chewing gum on oral environment (salivary parameters: hydration status of the labial mucosa, salivary resting pH, stimulated flow rate, buffering capacity; plaque pH and oral hygiene status) among Malaysian infantry personnel involved in military operation in the jungle near Malaysia-Thailand border. MATERIALS AND METHODS: A community intervention study was conducted on 309 Malaysian infantry personnel who were assigned into a control group (n=147) and an intervention group (n=162). The intervention group consumed xylitol chewing gum for 5 minutes, three times a day for the period of the military operation (2 months). The daily dose was 6.0grams. The respondents underwent saliva testing, followed by oral examination and plaque test. Saliva parameters and plaque pH were assessed using Saliva-Check BUFFER and Plaque - Check +pH (GC Corporation, Japan) respectively, while oral hygiene status was measured using Simplified Oral Hygiene Index (OHI-S). The baseline data recorded a few days before undergoing military operation were compared with the data recorded after 2 months. Independent t, Chi square, Fisher’s Exact and McNemar tests were applied during univariable analysis. Repeated measures ANOVA was utilised to analyse the differences and changes in means between, within and within between groups while repeated measures analysis of covariance (RM ANCOVA) was used during multivariable analysis to control for confounders. RESULTS: There was a significant change of hydration status with time of intervention among respondents in both groups (p<0.05). Higher proportion of respondents with better hydration status was found in the intervention group after intervention period. There were significant increases in mean buffering capacity and mean plaque pH and a significant decrease in mean OHI-S among respondents in the intervention group after the intervention period (p<0.001). There were significant drop in mean resting pH (p=0.008), mean buffering capacity (p=0.012) and mean plaque pH (p<0.001) and a significant increase in mean OHI-S (p<0.001) among respondents in the control group. No significant change was found in mean resting pH in the intervention group and in mean stimulated flow rate in both groups after intervention period. In terms of between groups, respondents in intervention groups had significantly higher mean buffering capacity, 8.50 (95% CI: 8.01, 8.98) and mean plaque pH, 6.20 (95% CI: 6.14, 6.25) compared to control group, 7.12 (95% CI: 6.65, 7.58); 5.95 (95% CI: 5.91, 6.00) (p<0.001). In terms of group effect with regard to time, there were significant differences in mean buffering capacity, mean plaque pH and mean OHI-S between intervention and control groups after intervention period. CONCLUSION: Chewing xylitol gum can protect the oral health of infantry personnel during military operation in the jungle by improving their hydration status, buffering capacity, plaque pH and OHI-S.